SISTEM INFORMASI MONITORING DOKUMEN PERMOHONAN DENGAN METODE KANO - IBNU PURNAMA (PT Triputra Sejahtera Prima, 2023)
With the rapid progress of the times where companies are required to be able to present information quickly and accurately, to improve performance and efficiency both time and cost, in order to achieve that, companies need an information system that is able to manage data properly. In practice, the company where the researcher works, namely PT. Cakrawala Gemilang Consultants experienced problems in the form of the difficulty of monitoring each application file submitted because the monitoring process carried out still used a manual control card in the form of paper containing company profiles and applications submitted, so that when the leadership wanted a report on the progress of the application, it took a long time to compile the report. The types of applications submitted are in the form of licensing and non-licensing applications. For information that PT. Cakrawala Gemilang Consultants is a consulting company in the field of licensing and non-licensing. To overcome the above problems, we need an information system that can monitor application documents so that it is expected to be able to provide information quickly and accurately. In this study, researchers used the Kano method to obtain data on user needs while for system development using the SDLC, namely the Waterfall model and for testing the system using the white box testing and black box testing methods.